Intrahepatic Stones: The Percutaneous Approach - Horst Neuhaus (Canadian Journal of Gastroenterology)
Intrahepatic stones are prevalent in the Far East, whereas they are infrequently seen in Western countries. Hepatolithiasis can cause recurrent attacks of cholangitis, with a risk of liver abscesses, sepsis or hepatic failure. Immediate biliary decompression can usually be achieved by endoscopic or percutaneous transhepatic drainage. Definitive treatment should aim for complete elimination of bile stasis and removal of all stones. Hepatic resection promises the best long term results when the disease is limited to segments or the left liver lobe. Endoscopic retrograde choledochopancreatography is not well established for intrahepatic stones because of frequent failures due to associated biliary strictures, angulated ducts or peripherally impacted concrements. In contrast, percutaneous procedures can be easily performed through a T tube tract for residual stones after surgery. Establishment of a transhepatic fistula allows a targeted approach to liver segments with catheters or miniscopes, without the need for laparotomy. Biliary strictures can be dilated with balloons, and intrahepatic stones can be removed with baskets under fluoroscopic or cholangioscopic control. These techniques can be combined with electrohydraulic lithotripsy or laser lithotripsy for disintegration of impacted calculi. The risk of stone recurrence is particularly high in patients with associated biliary stenoses. Temporary or long term transhepatic intubation is a promising approach in these cases. The optimal management of intrahepatic stones remains a challenging task that requires an experienced team of gastroenterologists, surgeons and radiologists.